Evaluation of the Scottish Prison Service Transitional Care Initiative - MacRae, Rhoda (Scottish Executive, 2006)
In June 2000 the Scottish Prison Service (SPS) launched a revised drug strategy aimed at, among other things, effectively managing the transition between prison and the community. Transitional Care was introduced by SPS in 2001 to support short-term prisoners (that is, those serving less than 4 years) and remand prisoners with an identified substance misuse problem. The main aim of Transitional Care was to facilitate access to pre-existing community services based on an individual’s assessed needs. This was done through the provision of support during a 12-week period immediately following a prisoner’s return to the community. The Transitional Care arrangements were provided by Cranstoun Drug Services under contract to SPS. A research team from the University of Stirling and TNS Social Research was commissioned to evaluate the operation and effectiveness of the Transitional Care initiative. A combination of quantitative and qualitative research methods was employed in this study. This included the analysis of Transitional Care monitoring data; surveys of prisoners four and seven months following release; in-depth interviews with ex-prisoners in three areas of the country with different demographic characteristics and varying arrangements for the delivery of Transitional Care; and interviews with prison and community based staff associated with Transitional Care. Interviews with prisoners included both those who had attended Transitional Care on release from prison and those who had not.